Niat Investasi Cryptocurrency di Indonesia - Nur Hendriawan, Brian; Mustiko Aji, Hendy (Jurnal Etnik: Ekonomi-Teknik, 2022)
This study aims to find out what are the factors that drive consumerperceptions of young Indonesian Muslims towards cryptocurrencyinvestment intentions. The sample in this respondent was selectedusing a purposive sampling technique with the criteria of consumersbeing Muslim. The number of valid respondents was 120. All datawere analyzed using the PLS-SEM method. The variables used inthis study are product knowledge, perceived quality, perceived risk,and behavioral intention. The results of this study indicate that theeffect of product knowledge has a positive effect on the perceptionof the quality of young Muslims towards cryptocurrency investment,product knowledge has a positive effect on the risk perception ofyoung Muslims towards cryptocurrency investment, and theperception of quality has a positive effect on the intentions of youngMuslims. Muslims towards cryptocurrency investment, Riskperception has a negative effect on the intentions of young Muslimstowards the use of cryptocurrency investments, Product knowledgehas a positive effect on the investment intentions of young Muslimstowards cryptocurrency investment. pay more attention to halalsensitivity and have an MUI halal certificate, so that Muslimconsumers can have an interest in cryptocurrency investment.